Review on the potential of endophytic microorganisms as biological control agents of cocoa diseases / Sitti Raihana Bazilah Bacho - Bazilah Bacho, Sitti Raihana (Faculty of Plantation and Agrotechnology, 2016)
This review paper aims to discuss on the potential of endophytic microorganism as bio-control agents to control cocoadiseases. The review covers four main topics which are (i) the current production of cocoa in Malaysia, (ii) the role of endophytic fungi and (iii) bacteria as biological control cocoa diseases and (iv) the future direction of biological control of the diseases using endophytes. Fungal pathogens are the major group affecting the cocoa crops and give negative impact on bean production. There are several approaches have been employed to control the diseases such as cultural, chemical and biological controls. Research and development towards production of reliable biological products are getting much attention among researchers. The application of endophytic microorganisms as biological control agents to combat cocoa diseases is well explored as the microorganisms show big potential to inhibit the growth of pathogens through multiple mechanisms.